Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar PKN di SDI Harekakae pada Siswa Kelas IV Tahun Pelajaran 2024/2025 - Maksimelianus Seran; Marsela Luruk Bere; Yanuarius Bria Seran; Damian Puling (Jurnal Pendidikan Dirgantara, 2025)
This study aims to determine the application of the Problem-Based Learning (PBL) model in improving Civic Education (PKn) learning outcomes among fourth-grade students at SDI Harekakae, Malaka Regency. This research employed an experimental method using a post-test only control group design. The population consisted of all fourth-grade students, with class IV B serving as the experimental group and class IV C as the control group, totaling 42 students. The experimental group was taught using the Problem-Based Learning model, while the control group was taught without applying the model. Data were collected through learning outcome tests, observations, and documentation. The results showed that the experimental class achieved an average score of 85 out of an ideal score of 100 with a standard deviation of 8.25, while the control class obtained an average score of 62.6. These findings indicate that the implementation of the Problem-Based Learning model significantly improves students’ Civic Education learning outcomes. Therefore, the Problem-Based Learning model is recommended as an innovative alternative to enhance the effectiveness of Civic Education learning in elementary schools.